How do expert soccer players encode visual information to make decisions in simulated game situations? - Poplu, G.; Ripoll, H.; Mavromatis, S.; Baratgin, J. (Research Quarterly for Exercise and Sport, 2008)
The aim of this study was to determine what visual information expert soccer players encode when they are asked to make a decision. We used a repetition-priming paradigm to test the hypothesis that experts encode a soccer pattern`s structure independently of the players` physical characteristics (i.e., posture and morphology). The participants were given either realistic (digital photos) or abstract (three-dimensional schematic representations) soccer game patterns. The results showed that the experts benefited from priming effects regardless of how abstract the stimuli were. This suggests that an abstract representation of a realistic pattern (i.e., one that does not include visual information related to the players` physical characteristics) is sufficient to activate experts` specific knowledge during decision making. These results seem to show that expert soccer players encode and store abstract representations of visual patterns in memory.